Integrated biomimetic carbon nanotube composites for in vivo systems. - Kumar Singh, MK (2010)
As interest in using carbon nanotubes for developing biologically compatible systems continues to grow, biological inspiration is stimulating new directions for in vivo approaches. The ability to integrate nanotechnology-based systems in the body will provide greater successes if the implanted material is made to mimic elements of the biological milieu especially through tuning physical and chemical characteristics. Here, we demonstrate the highly successful capacity for in vivo implantation of a new carbon nanotube-based composite that is, itself, integrated with a hydroxyapatite-polymethyl methacrylate to create a nanocomposite. The success of this approach is grounded in finely tailoring the physical and chemical properties of this composite for the critical demands of biological integration. This is accomplished through controlling the surface modification scheme, which affects the interactions between carbon nanotubes and the hydroxyapatite-polymethyl methacrylate. Furthermore, we carefully examine cellular response with respect to adhesion and proliferation to examine in vitro compatibility capacity. Our results indicate that this new composite accelerates cell maturation through providing a mechanically competent bone matrix; this likely facilitates osteointegration in vivo. We believe that these results will have applications in a diversity of areas including carbon nanotube, regeneration, chemistry, and engineering research.